The Dynamics of Foreign Language Enjoyment: An Ecological Momentary Assessment - Elahi Shirvan, Majid; Taherian, Tahereh; Yazdanmehr, Elham (Frontiers in Psychology, 2020)
Following the recent shift from negative psychology to positive psychology, interest in foreign language enjoyment has grown noticeably in second language acquisition. Given the fact that learners are “persons-in-context” and are not “ergodic ensembles”, the particular learner-context ecosystem goes through ongoing momentary changes with respect to individual differences like foreign language enjoyment. Ecological momentary assessment contributes to our understanding of the dynamics of this ecosystem in terms of the interaction between individual learners and their learning environments. In this study, using a time based sampling scheme of ecological momentary assessment, we explored the dynamism of different facets of foreign language enjoyment across different time scales including seconds, minutes, weeks, and months in a course of intermediate English as a foreign language. To do this, we applied open-ended interviews with two intermediate English language learners in a private English language institute across months, journals across weeks, enjoymeters across minutes, and the idiodynamic approach across seconds. Findings indicated that enjoyment in foreign language fluctuates in terms of a hierarchy of temporal scales, from moment-to-moment changes to the ones over months. The emerging patterns of enjoyment across different time scales in terms of the tenets of complex dynamic systems theory are discussed.